2006
DOI: 10.1152/jn.00981.2005
|View full text |Cite
|
Sign up to set email alerts
|

Partial Cross-Correlation Analysis Resolves Ambiguity in the Encoding of Multiple Movement Features

Abstract: A classical question in neuroscience is which features of a stimulus or of an action are represented in brain activity. When several features are interdependent either at a given point in time or at distinct points in time, neural activity related to one feature appears to be correlated with other features. Thus techniques that simultaneously consider multiple features cannot account for delayed interdependencies between features. The result is an ambiguity with respect to the encoded features. Here, we resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 23 publications
0
42
0
1
Order By: Relevance
“…In this analysis, we followed the method described by Stark et al (2006) with the exception that we segmented our continuous data into relatively short epochs of equal lengths rather than organizing it by trials. Like the LFP data, binned time series representing instantaneous cursor and eye directions were concatenated across blocks of each condition and truncated to the length of the shortest condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this analysis, we followed the method described by Stark et al (2006) with the exception that we segmented our continuous data into relatively short epochs of equal lengths rather than organizing it by trials. Like the LFP data, binned time series representing instantaneous cursor and eye directions were concatenated across blocks of each condition and truncated to the length of the shortest condition.…”
Section: Discussionmentioning
confidence: 99%
“…We found that, especially in the cursor and target and target-only observation conditions, eye movements were highly correlated with the cursor movements, raising the possibility that the apparent correlation between neural activity and cursor movement we saw during observation was an indirect consequence of the correlation between neural activity and eye movements. To assess the degree to which the observed neural activity was independently related to eye or cursor movement, we followed the method described by Stark et al (2006). They rely on the method of partial correlations (Fisher, 1970) to assess the residual correlation between two variables when linear correlations with a third variable have been removed, and they expand the method to take into account multiple temporal leads and lags between two variables.…”
Section: Eye Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, simple correlation is not suitable for evaluating effects of variables H t , L t , and S t on population dynamics. Partial cross correlation has been widely used for causal analysis by controlling co-varying variables (Stark et al 2006). Partial cross correlation is very useful for inferring direct or spurious causes of control variables.…”
Section: Discussionmentioning
confidence: 99%
“…A third monkey (F) was trained to perform continuous curved movements with its preferred left hand by operating a two-joint low-friction planar manipulandum (Stark et al, 2006). A horizontal opaque screen, mounted at chest level, blocked view of manipulandum and hand, and a yellow cursor indicating hand end-point was projected on the screen (see Fig.…”
Section: Methodsmentioning
confidence: 99%